Effect of hydrothermal time on the hydrochar characteristics of galam (Malaleuca leucadendra) bark and application tests as methylene blue adsorbent - Sunardi Sunardi, Ph.D.; Risaldi Ridwan; Hanna Habibah; Desmalina Safitri; Utami Irawati (Jurnal Riset Industri Hasil Hutan, 2022)
Production of galam wood produces bark waste that is disposed in around of the production site without processing. The use of galam bark waste is very necessary to reduce waste and its problems in the environment and optimize the potential of galam wood as a typical Kalimantan plant. In this research, modification of galam bark biomass (Malaleuca leucadendra) into hydrochar through a hydrothermal process with variations of hydrothermal time and its use for methylene blue adsorbent has been done. The hydrothermal process was carried out at the temperature of 200˚C for 3 hours, 6 hours, and 12 hours. The characterization of hydrochar substrate using FTIR (Fourier Transform Infrared Spectroscopy) showed the decrease in absorption intensity of 47% and a shift in several wavenumbers. The characterization using SEM (Scanning Electron Microscope) showed that there are morphological changes on the surface of the hydrochar become to more holes after the hydrothermal process. The optimum condition for adsorption occurred at pH 7 for 10 minutes. The adsorption capacity of methylene blue increased from 44.70 mg/g to 45.82, 46.17, and 46.90 mg/g after hydrothermal process. The results also showed that the adsorption followed the Freundlich isothrm which showed a tendency for multilayer interactions on the surface of the galam barks after the hydrothermal process.